Penyuluhan Hukum Tentang Pemilihan Umum Kepada Pemilih Pemula Sma Madani Al-Aziziyah - Syukriah Syukriah; Afifuddin Afifuddin; Vonna Hasyimi; Vena Savera (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Article 198 paragraph (1) of Law Number 7 of 2017 concerning Elections Chapter IV, initial voters are Indonesian citizens who are 17 years old or more on voting day or are already married, who have the right to vote. In the 2024 simultaneous elections, the number of young voters is expected to increase. If guided by the 2019 election, KPU figures show that out of 193 million voters, the number of young voters reached 70-80 million. This means that 35% -40% of young voters have a big influence on the election results, which in turn affects the progress of the country. However, another potential problem for participating young voters is that they also have the opportunity to become contributors to